Preface - Fernandes, Geni Chaves (2015)
Studies are pointing to changes in scientific knowledge production systems regarding different models (mode2, triple helix, actor-network, post-academic etc.), emphasizing its interdisciplinary, multiplayer and multiplace characteristics. When seeking an explanation of reality, models create interpretive images that interfere in the reality, as they operate offering parameters to actions. The differences and implicit forecasts they present point not only to local, cultural or ideological burdens in its construction, but especially that the different intervening forces have not yet found stability, indicating that we are still going through a time of transition.